Development of Space Launch Vehicles in India. Issue 2 (1st September 2016) - Nagappa, Rajaram
ABSTRACT: The Indian space program is a spacefaring success story with demonstrated capability in the design and building of application and scientific satellites, and the means to launch them into desired orbits. The end-to-end mission planning and execution capability comes with a high emphasis on self-reliance. Sounding rockets and small satellite launch vehicles provided the initial experience base for India. This experience was consolidated and applied to realize larger satellite launch vehicles. While many of the launch vehicle technologies were indigenously developed, the foreign acquisition of liquid propulsion technologies did help in catalyzing the development efforts. In this case, launch vehicle concept studies showed the inevitability of using a cryogenic upper stage for geosynchronous Earth orbit missions, which proved to be difficult technically and encountered substantial delays, given the geopolitical situation. However, launch capability matured from development to operational phases, and today, India's Polar Satellite Launch Vehicle and Geosynchronous Satellite Launch Vehicle are in a position to meet both domestic and international market demands.